Mg3B7O13Cl: A New Quasi‐Phase Matching Crystal in the Deep‐Ultraviolet Region. (24th August 2018) - Wang, Zujian; Qiao, Huimin; Su, Rongbing; Hu, Bing; Yang, Xiaoming; He, Chao; Long, Xifa
Abstract: Deep‐ultraviolet lasers play an important role in many scientific and technical fields, the generation of which by means of the nonlinear optical frequency conversion technology attracted immense research interest over the past few decades. Up to now, there are few nonlinear optical crystals, except KBe2 BO3 F2, which could produce deep‐ultraviolet coherent light by a harmonic generation process. However, industrialization of KBe2 BO3 F2 is hampered by its layering growth habit and weak interlayer force. Here, a new deep‐ultraviolet nonlinear optical crystal, Mg3 B7 O13 Cl, is found, which will be a good candidate for deep‐ultraviolet coherent generation. It crystallizes an acentric space group of Pca 21 at room temperature with both 3D borate frameworks and distorted octahedrons, which makes it a unity of optical nonlinearity and ferroelectricity. Furthermore, a short absorption cutoff of 155 nm, a second harmonic generation coefficient of 0.38 pm V −1, a coercive field of 21.2 kV cm −1, and a remanent polarization of 0.36 µC cm −2 for Mg3 B7 O13 Cl crystal are identified. These features indicate that Mg3 B7 O13 Cl crystal can generate deep‐ultraviolet coherent light by a quasi‐phase matching technique with a periodically poling method. This pioneering and profound work points out a new research area in the development of deep‐ultraviolet lasers. Abstract : A new deep‐ultraviolet nonlinear optical crystal, Mg3 B7 O13 Cl, is found with both 3D borate frameworks and distorted octahedrons, which make it a unity of optical nonlinearity and ferroelectricity with a short absorption cutoff of 155 nm. These features indicate that the Mg3 B7 O13 Cl crystal can generate deep‐ultraviolet coherent light by a quasi‐phase matching technique with a periodically poling method.